HISTORY OF COMPOSITE MATERIALS - Zhuzbayev С.С.; А.Қ; Akhmetzhanova Ш.Е. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This article discusses the discovery and creation of composite materials, general characteristics and differences, structure, purpose of structural materials, a special combination of strength, stiffness and lightness, composite materials regardless of their origin, the result of volumetric combinations of various components, without individual components. properties, continuous component in the volume of composite materials - matrix, types of materials and their classification, composite building materials. Also reinforced building materials, the properties of many materials around us, their features, the properties of composite materials, their use in all fields of science, technology, industry, the ability to adjust the properties of composite materials using several matrices or fillers of different nature, the strength of the composite, hardness and deformation, composite materials with special properties.